Survival of infants and children born with severe microcephaly, Texas, 1999–2015. Issue 1 (8th November 2022) - Marengo, Lisa K.; Archer, Natalie; Shumate, Charlie; Canfield, Mark A.; Drummond‐Borg, Margaret
Abstract: Background: Severe microcephaly is a brain reduction defect where the delivery head circumference is <3rd percentile for gestational age and sex with subsequent lifelong morbidities. Our objective was to evaluate survival among 2, 704 Texas infants with severe microcephaly delivered 1999–2015. Methods: Infants with severe microcephaly from the Texas Birth Defects Registry were linked to death certificates and the national death index. Survival estimates, hazard ratios (HR) and confidence intervals (CI) were calculated using the Kaplan–Meier method and Cox proportional hazards models stratified by presence versus absence of co‐occurring defects. Results: We identified 496 deaths by age 4 years; most (42.9%) occurred in the neonatal period, and another 39.9% died by 1 year of age. Overall infant survival was 84.8%. Lowest infant survival subgroups included those with chromosomal/syndromic conditions (66.1%), very preterm deliveries (63.9%), or co‐occurring critical congenital heart defects (44.0%). Among infants with severe microcephaly and a chromosomal/syndromic co‐occurring defect, the risk of death was nearly three‐fold higher among those with: proportionate microcephaly (i.e., small baby overall), relative to non‐proportionate (HR = 2.84, 95% CI = 2.17–3.71); low‐birthweight relative to normal (HR = 2.72, 95% CI = 1.92–3.85); critical congenital heart defects (CCHD) relative to no CCHD (HR = 2.90, 95% CI = 2.20–3.80). Trisomies were a leading underlying cause of death (27.5%). Conclusions: Overall, infants with severe microcephaly had high 4‐year survival rates which varied by the presence of co‐occurring defects. Infants with co‐occurring chromosomal/syndromic anomalies have a higher risk of death by age one than those without any co‐occurring birth defects.